Lignin Nanoparticles Comparative Study for their Emulsifying, Antibacterial and Antioxidant Properties - Ebaid, Matta Asaad Mesak (AUC Knowledge Fountain, 2023)
Converting lignin, the second most natural abundant polymer on earth, into lignin nanoparticles (LNPs) form has potential applications. LNPs’ emulsifying, antibacterial and antioxidant properties of three different lignins, softwood kraft lignoboost (LB), hardwood birch (BB) and alkali protobind 1000 (PB) were evaluated in a comparative study at different pH and concentrations. Lower ionic strength of 5 millimole (mM) citric acid (CA) and pH of 7 were found to be the most optimum conditions for emulsion formation. Comparison among the two homogenization techniques revealed that microfluidizer is favored in case of BB- and PB-LNPs based emulsions, while ultrasonication is optimum in case of LB-LNPs based emulsions. LNPs’ concentrations were found directly in proportion with their emulsifying activity to stabilize emulsions. LNPs based rapeseed oil (RO)/water emulsions showed slightly better yield than LNPs based hexadecane (HD)/water emulsions in terms of particle size distribution (PSD) in PB-LNPs and LB-LNPs based samples while the opposite in case BB-LNPs emulsions. As an emulsifier, PB-LNPs showed the highest effect versus LP- LNPs least effective. In terms of antioxidant activity, BB-LNPs showed the highest effect represented by 83 % of 2,2-diphenyl-1-picrylhydrazyl (DPPH) inhibition while LB-LNPs’ DPPH inhibition was the lowest by 67 at 0.5 w/w% LNPs concentration. Microbiologically, LNPs exhibited strong inhibition against gram positive Staphylococcus aureus by achieving 3 logs of reduction; however, found less effective against gram negative Escherichia coli (E. coli) without major reduction. This study expands on the potential applications of LNPs to be employed in food, agriculture, and pharmaceutical industries.